Esensi Pendidikan Karakter Berbasis Budaya Di Sekolah Dasar - Cahyani, Elvima Putri Nur; Dwinata, Anggara; Adlina, Nuha; Pujiono, Slamet (Discovery, 2024)
The role of character education in 21st Century learning can’t be ignored, considering the occurrence of apathetic and individualistic attitudes, the widespread use of gadgets over time, and the rise of sexuality which has become a serious problem because character is not massively implemented in humans. The aim of the research is to effectively realize culture-based character education in the elementary school environment through noble values in elementary schools. The research method used is a literature review study by reviewing several articles in national scientific research journals. Data collection techniques in research were carried out by collecting various articles relevant to the study topic. The findings in the study provide an explanation of the importance of character education built through a school culture. Implementing character education based on school culture is the goal and function of overcoming the impact of globalization and the moral degradation of the nation's generation. With character education integrated with school culture, it is hoped that it can instill noble values and positive habits in students.